Correction: High-performance liquid chromatographic method for determination of voriconazole in pure and gel formulation. - Samina Sheikh; Anwar Ejaz Beg; Mirza Tasawer Baig; Sadaf Ibrahim; Ambreen Huma; Aisha Jabeen; Zubair Anwar (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0315704.].